KONTRIBUSI PEDAGANG KAKI LIMA MAKANAN TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) ; STUDI KASUS DI KOTA MAGELANG - Khikmah, Siti Noor; Yuliani, Nur Laila (Jurnal Analisis Bisnis Ekonomi, 2009)
This research aim to know the influence education and training, management capital, income for natural regional income. This Education and training population are PKL in Magelang City. This research of sample as much 61 PKL and that can researched as much 54 respondent used with the method of convinience sampling. The result of the study denied one and two hypothesis, and the archieved of third hypothesis. The result has shows that studying and training don't effect management capital, management capital don't effect for income, while income is effected for natural regional income.